2013
DOI: 10.1111/trf.12303
|View full text |Cite
|
Sign up to set email alerts
|

Segments from red blood cell units should not be used for quality testing

Abstract: The quality of samples from tubing segments is not representative of the quality of the corresponding RBC unit. Segments are not suitable surrogates with which to assess RBC quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…We tested if bag versus segment differences exist in nitrite oxidation kinetics; however, no differences were observed with the exception of slightly slower rates in the lag phase in segments. Interestingly, segment‐bag differences in hemolysis were observed with a trend toward increased Hb in the segment, consistent with published reports . In contrast, free heme was higher in the bags compared to segments.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We tested if bag versus segment differences exist in nitrite oxidation kinetics; however, no differences were observed with the exception of slightly slower rates in the lag phase in segments. Interestingly, segment‐bag differences in hemolysis were observed with a trend toward increased Hb in the segment, consistent with published reports . In contrast, free heme was higher in the bags compared to segments.…”
Section: Discussionsupporting
confidence: 90%
“…Figures 7D and 7E show that there was a modest increase in hemolysisderived Hb from Day 35 to Day 42 in segments, but no changes in free heme. Interestingly, while a trend toward increase Hb in the segments vs bags was observed, consistent with previous studies, 33 the opposite was observed for free heme (Fig. 7E).…”
Section: Bag Versus Segment Samplingsupporting
confidence: 92%
See 2 more Smart Citations
“…A limitation in our measurements is that for human RBCs, we quantitated storage-dependent free heme and Hb formation from segments that are attached to RBC bags. Recent studies have shown that segments have higher levels of hemolysis relative to the paired bag, and our data demonstrated differences in complement levels also, but with levels being higher in the bag relative to the segment [37, 38]. Further studies evaluating cell-free heme formation in bags vs. segments is required.…”
Section: Discussionmentioning
confidence: 58%